Review & Penyesuaian SOP di PT Inserasena oleh Departemen Export Import Persiapan Menuju ke Perusahaan Penerima Fasilitas Kawasan Berikat - Anthony Gunawan; Jani Rahardjo (Jurnal Titra, 2023)
Market conditions are constantly changing, PT Inserasena plans to switch to becoming a company receiving Bonded Zone facilities from the previous KITE (Kemudahan Impor tujuan Ekspor) Return. The purpose of this transition is to maximize profits by accelerating cash flow and increasing production. Therefore, this study aims to prepare for the transition and fulfillment of the requirements by the provisions in bonded zones. This research was carried out by reviewing, brainstorming, and repairing and adjusting the Company's Internal Control System / Standard Operating Procedures related to the flow of goods in and out to fulfill the provisions in the Bonded Zone accompanied by the Export and Import Department. Based on the research results it is known that there are several SOPs documented in the ISO 9001: 2015 documentthat has not been updated with the actual work process, out of a total of 59 SOPs after adjustments, additions and reductions to 64 SOPs that are by Bonded Zone requirements and have been verified & validation with related departments and for departmental SOPs that experience significant adjustments are the Export-Import Department.